An updated understanding of the mechanisms involved in chemotherapy-induced neuropathy. (13th September 2018) - Boyette-Davis, Jessica A; Hou, Saiyun; Abdi, Salahadin; Dougherty, Patrick M
The burdensome condition of chemotherapy-induced peripheral neuropathy occurs with various chemotherapeutics, including bortezomib, oxaliplatin, paclitaxel and vincristine. The symptoms, which include pain, numbness, tingling and loss of motor function, can result in therapy titrations that compromise therapy efficacy. Understanding the mechanisms of chemotherapy-induced peripheral neuropathy is therefore essential, yet incompletely understood. The literature presented here will address a multitude of molecular and cellular mechanisms, beginning with the most well-understood cellular and molecular-level changes. These modifications include alterations in voltage-gated ion channels, neurochemical transmission, organelle function and intracellular pathways. System-level alterations, including changes to glial cells and cytokine activation are also explored. Finally, we present research on the current understanding of genetic contributions to this condition. Suggestions for future research are provided.